Advances in Cryogenic Engineering 1971
DOI: 10.1007/978-1-4757-0244-6_55
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Behavior of Liquid-Nitrogen Drops in Film Boiling

Abstract: An asymptotic expression for the vaporization time of large drops in film boiling has been derived. This expression seems to correlate the nitrogen data. Also, a new expression for the modified latent heat of vaporization is derived. This expression is useful for large temperature gradients occurring within the vapor film supporting the drop o r for fluids having small latent heats such as would occur for cryogens o r ordinary fluids near the thermodynamic critical point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Evaporation of individual liquid nitrogen droplets on a metal plate was studied by Keshock & Bell (1970), Baumeister, Keshock & Pucci (1971), Schoessow, Chmielewski & Baumeister (1978). Hassan (1981) and Awonorin (1982) measured evaporation times and droplet size in contact with food.…”
mentioning
confidence: 99%
“…Evaporation of individual liquid nitrogen droplets on a metal plate was studied by Keshock & Bell (1970), Baumeister, Keshock & Pucci (1971), Schoessow, Chmielewski & Baumeister (1978). Hassan (1981) and Awonorin (1982) measured evaporation times and droplet size in contact with food.…”
mentioning
confidence: 99%
“…They attributed this increase to the shorter vaporization times of droplets, vapour instabilities, low latent heat of vaporization and convection effects. Baumeister, Keshock and Pucci (1971) further developed expressions for the heat transfer coefficient by taking account of the latent heat of vaporization for liquid nitrogen, but the measured vaporization times were still lower than those predicted theoretically. Schoessow, Chmielewski and Baumeister (1978) concluded that contamination of nitrogen by ice at the early stages of droplets' formation, and convection effects account for approximately 20% of the vaporization times.…”
Section: Introductionmentioning
confidence: 95%